Heterojunction engineering of Ni3S2/NiS nanowire for electrochemical hydrogen evolution. (1st January 2023) - Chen, Meng; Su, Qing; Kitiphatpiboon, Nutthaphak; Zhang, Juan; Feng, Changrui; Li, Shasha; Zhao, Qiang; Abudula, Abuliti; Ma, Yufei; Guan, Guoqing
Graphical abstract: Highlights: Ni3 S2 @NiS nanowire with heterojunction was created as electrocatalyst for HER. NiS was epitaxially grown on the surface of Ni3 S2 via a solid-state phase transformation. The strong charge transfer at Ni3 S2 /NiS heterojunction interface optimized the d-band center. Ni3 S2 @NiS-250/NF electrode revealed high HER activity and stability. Abstract: Hydrogen evolution reaction (HER) over the non-noble metal-based electrocatalysts is a promising approach to realize future clean energy economy. Herein, to achieve effective interface construction, epitaxial growth of NiS on the surface of one-dimensional (1D) Ni3 S2 nanowire on nickel foam (NF) was performed, to construct a Ni3 S2 /NiS electrocatalyst with a heterojunction structure via a solid-state phase transformation. Benefiting from the strong charge transfer at the Ni3 S2 /NiS heterojunction interface, the d-band center was downshifted compared to the single component (Ni3 S2 or NiS), which effectively optimized the valence state and the H adsorption of Ni, thus improved the HER activity. The obtained Ni3 S2 @NiS-250/NF showed the robust HER catalytic performance with a low overpotential of 129 mV to deliver the current density of 10 mA cm −2 with a small Tafel slope (75.5 mV dec -1 ) in 1 M KOH media. Moreover, it exhibited superior durability for at least 50 h. This work provides a novel strategy for designing nickel sulfide-based catalysts for HER with high performance.